If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-14-2p=8(-p-7)
We move all terms to the left:
-14-2p-(8(-p-7))=0
We add all the numbers together, and all the variables
-2p-(8(-1p-7))-14=0
We calculate terms in parentheses: -(8(-1p-7)), so:We get rid of parentheses
8(-1p-7)
We multiply parentheses
-8p-56
Back to the equation:
-(-8p-56)
-2p+8p+56-14=0
We add all the numbers together, and all the variables
6p+42=0
We move all terms containing p to the left, all other terms to the right
6p=-42
p=-42/6
p=-7
| x/5-3=x/15-5 | | 8v=4v+36 | | ∣3g∣−4=11 | | -7v-39=3(1-7v) | | 28=d−7 | | 4=2.5x+7.5 | | (4/x)^2=16/25= | | v/8+30=26 | | 16x=+12 | | -x=-7x+6 | | 2x/3=8/12 | | m/6-(-43)=53 | | -92=-4-4(2+4x) | | 4(3x-1)=2x-4 | | -9(x+15)=13+-11x | | |5w=15|=5 | | -2(x+1)=5x+3x+9 | | x(.085)=55000 | | y2+22=31 | | 5/3=u-2/2 | | -3(6f+6)=-2(10f+7) | | -8x+6(x+2)=32 | | 2(y-4)-10=-2 | | 3(x+5)=-7+13x | | 3x+7=2x9 | | 2.27(u-6)+1.86=8.67 | | -5=2(r+3)+3 | | -5(-5x+12)=+6x=95 | | 9-r=-8(-r-9) | | -3-6w-9w=-6(4w-7) | | 0.2x3+1.6=0 | | 75=5x-3(-3x=3) |